Komparasi Pemahaman Konsep Siswa yang Diajar dengan Metode Mind Mapping dan Metode Guided Note Taking pada Kelas VIII SMP - Ishaq Munajah; Ilham Minggi; Ahmad Talib (Issues in Mathematics Education (IMED), 2020)
This study was an experimental study involving two treated groups. This study aims to find out a differences in understanding of mathematical concepts between students taught using the Mind Mapping method and the Guided Note Taking method. The study sample consisted of two classes selected using the cluster random sampling technique . Data collection is done by using observation sheets and concept understanding test instruments. Data collected was analyzed descriptively and inferentially. The results showed that there are significant differences between increasing understanding of mathematical concepts of students taught by Mind Mapping learning methods and students taught using Guided Note Taking learning methods in class VIII.